A case of kidney graft injury during cesarean section in a pancreas and kidney transplantation recipient - Noriko Aida; Eiji Nishio; Takao Sekiya; Naohiro Aida; Taihei Ito; Takashi Kenmochi; Haruki Nishizawa (Fujita Medical Journal)
Although organ transplantation is becoming general practice, little is known about the safety of delivery. This is the first known case that describes injury to the kidney by the uterine fundal pressure maneuver during cesarean section in a pancreas and kidney transplant recipient. A 40-year-old pregnant woman (gravida 0, para 0) was referred to our clinic. She had undergone living donor kidney transplantation 11 years earlier and brain-dead donor pancreas transplantation 1 year earlier owing to type 1 diabetes. Cesarean section was indicated when the patient’s blood pressure was 150/100 mmHg at 37 weeks. We pushed the uterine fundus during delivery of the infant, with our usual caution. Serum creatinine levels were 1.6–2.6 mg/dl postoperatively. As this elevation was considered to be due to kidney graft dysfunction, we performed computed tomography, which revealed a hematoma around the kidney graft. Fifteen days after the cesarean section, surgical removal of the hematoma was performed by the transplant surgery team. Following hematoma removal, the serum creatinine level decreased to <1.4 mg/dl. We present a case of kidney graft injury during cesarean section in a pancreas and kidney transplant recipient.